Gender Differences in Online High School Courses - Lowes, Susan; Lin, Peiyi; Kinghorn, Brian R.C. (Online Learning, 2016)
Prior research has suggested that there may be differences in the ways that male and female students approach their online courses. Using data for 802 high school students enrolled in 14 online courses, this study explored gender differences in the interrelationships among online behaviors and course performance. The findings show that females were more active than males and that a higher degree of online activity and discussion forum viewing and posting was associated with better final grades, but the correlation was stronger for males than it was for females. Further exploration of posting behaviors revealed that females who received lower final grades were more active than males who received lower grades—they viewed more posts, wrote more posts, and wrote longer posts. These gender differences have implications for researchers, course providers, and course designers.